1998
DOI: 10.1124/mol.54.3.569
|View full text |Cite
|
Sign up to set email alerts
|

α2C-Adrenoceptor-Overexpressing Mice Are Impaired in Executing Nonspatial and Spatial Escape Strategies

Abstract: Drugs acting via alpha2-adrenoceptors modulate cognitive functions mediated via frontostriatothalamic feedback loops. The alpha2C-adrenoceptor subtype is expressed in the basal ganglia, hippocampus, and neocortex, areas that are involved in memory and other cognitive functions. alpha2C-Overexpressing (OE) mice were impaired in spatial or nonspatial water maze (WM) tests, and alpha2 antagonist treatment fully reversed the WM escape defect in OE mice. However, alpha2C-overexpression did not influence open field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The a 2C subtype is widely distributed throughout the brain (Rosin et al 1996;MacDonald et al 1997) and several recent studies suggest that a 2C receptors are required for normal presynaptic control of transmitter release from central NE neurones Hein et al 1999). Furthermore, Bjorklund et al (1998) have shown that overexpression of a 2C receptors worsened spatial recognition which was reverted by a a 2C antagonist. a 2 antagonism of atypical NLs is also suggested to contribute to prefrontal DA increase as the a 2 antagonist idazoxan had the same effect (Gresch et al 1995;Hertel et al 1999).…”
Section: Discussionmentioning
confidence: 97%
“…The a 2C subtype is widely distributed throughout the brain (Rosin et al 1996;MacDonald et al 1997) and several recent studies suggest that a 2C receptors are required for normal presynaptic control of transmitter release from central NE neurones Hein et al 1999). Furthermore, Bjorklund et al (1998) have shown that overexpression of a 2C receptors worsened spatial recognition which was reverted by a a 2C antagonist. a 2 antagonism of atypical NLs is also suggested to contribute to prefrontal DA increase as the a 2 antagonist idazoxan had the same effect (Gresch et al 1995;Hertel et al 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Further evaluation of small differences between ␣ 2C KO and ␣ 2C WT mice suggested ␣ 2C AR participation in dexmedetomidine-induced hypothermia, dopamine metabolism, and d-amphetamine-induced hyperlocomotion (Rohrer and Kobilka, 1998). Confirmation of these subtle physiological differences was greatly aided through comparison of ␣ 2 AR agonist-mediated effects in ␣ 2C AR KO and ␣ 2C AR OE mice (Bjorklund et al, 1998;Sallinen et al, 1998a,b). These studies of subtle differences between ␣ 2C AR KO and ␣ 2C AR OE mice also revealed participation by the ␣ 2C AR in cardiovascular function (MacDonald et al, 1997), the startle reflex and aggression (Sallinen et al, 1998a,b), and complex navigation behavior (Bjorklund et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, only minimal differences in ␣ 2 AR agonist-induced responses (Link et al, 1996) were observed between ␣ 2C AR knockout (KO) and wild-type (WT) mice. Comparing the subtle differences among ␣ 2C AR-KO, ␣ 2C AR over-expresser (OE), and their respective WT control mice provided converging evidence that ␣ 2C ARs contribute to cardiovascular function (MacDonald et al, 1997) and several physiological processes (see Discussion, Bjorklund et al, 1998;Sallinen et al, 1998a,b). A role for ␣ 2C AR in analgesia has been previously suggested (Takano and Yaksh, 1993;Guo et al, 1999;Fairbanks and Wilcox, 1999;Graham et al, 2000) but not clearly established.…”
mentioning
confidence: 99%
“…Experiments in genetically altered mice show that overexpression of ␣ 2C receptors contributes to behavioral despair and accordingly, blockade of ␣ 2C receptors could be antidepressive . Other preclinical studies indicate that overexpression of ␣ 2C receptors worsens spatial recognition and induces anxiety-like behavior (Björklund et al 1998(Björklund et al , 1999. These effect were reverted by an ␣ 2 antagonist, suggesting that blockade of ␣ 2C receptors might result in improved cognition and anxiolytic activity.…”
Section: Affinity For ␣ 2a and ␣ 2c Adrenoceptorsmentioning
confidence: 98%